2007
DOI: 10.1007/s10765-007-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Measurements and Correlation of the Squalane + CO2 Mixture

Abstract: Experimental results for the viscosity of squalane + CO 2 mixtures are reported. The viscosities were measured using a rolling ball viscometer. The experimental temperatures were 293.15, 313.15, 333.15, and 353.15 K, and pressures were 10.0, 15.0, and 20.0 MPa. The CO 2 mole fraction of the mixtures varied from 0 to 0.417. The experimental uncertainties in viscosity were estimated to be within ±3.0%. The viscosity of the mixtures decreased with an increase in the CO 2 mole fraction. The experimental data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 12 publications
(17 reference statements)
6
56
2
1
Order By: Relevance
“…The baseline of figure 1 represents the correlated viscosity values. The average absolute deviations between our present viscosity data of squalane and those reported by Tomida et al [30] Kumagai et al [31] Kuss and Golly [32], Ciotta et al [33] and Pensado et al [18] are (1.2, 1.4, 1.1, 3.2 and 0.8)% respectively, whereas the maximum deviations are (3.5, 2.5, 1.9, 6.3 and 2.6)%. These deviations are similar to those usually indicated in articles concerning experimental studies of viscosity of fluids in broad ranges of pressure, even for low viscous fluids [34,35].…”
Section: Viscositysupporting
confidence: 52%
“…The baseline of figure 1 represents the correlated viscosity values. The average absolute deviations between our present viscosity data of squalane and those reported by Tomida et al [30] Kumagai et al [31] Kuss and Golly [32], Ciotta et al [33] and Pensado et al [18] are (1.2, 1.4, 1.1, 3.2 and 0.8)% respectively, whereas the maximum deviations are (3.5, 2.5, 1.9, 6.3 and 2.6)%. These deviations are similar to those usually indicated in articles concerning experimental studies of viscosity of fluids in broad ranges of pressure, even for low viscous fluids [34,35].…”
Section: Viscositysupporting
confidence: 52%
“…The specific features of the rolling-ball viscometer are digital angular positioning of the cell via a computer-controlled stepper motor (Oriental Motor Co. Ltd., ASM46AA-T20), a cell body that is constructed from light-weight titanium (JIS Class 2), a movable piston with position sensing by a linear-variable differential transformer (LVDT) (Shinko Denshi Co. Ltd., WA-2S and A22-3), and a sapphire window for visual observation. The apparatus uses the rolling-ball principle for measurements, since this method allows for the study of both low-and high-pressure measurements [2], and its principle has been confirmed for both paint and coating mixtures [3], CO 2 containing mixtures [4,5], and fluid mixtures at high pressures [6][7][8]. The digital angular positioning of the cell allows for highly reproducible initial conditions to within 0.05 • to be maintained.…”
Section: Methodsmentioning
confidence: 99%
“…The viscosities were measured with a rolling-ball viscometer, which has been described in detail elsewhere [6,22]. The glass tube was approximately 10 cm in length with an internal diameter of 7.15 mm or 7.30 mm (±0.01 mm), and the diameter of the stainless-steel ball was 7.00 mm (±0.01 mm).…”
Section: Measurementsmentioning
confidence: 99%